RATIONALITY EVALUATION OF ANTIBIOTIC USE IN PEDIATRIC PNEUMONIA AT HOSPITALS IN INDONESIA - Suminar, Fadhila Diah (Transpublika Publisher, 2022)
Indonesia is a developing country that has high morbidity and mortality rates due to infectious diseases, one of which is pneumonia. This study aims to describe the use of antibiotics, to determine the rationality of antibiotic use using the Gyssens method, and to determine the relationship between the rationality of antibiotic use on the therapeutic outcomes of pediatric pneumonia patients in one of the public hospitals and private hospitals in Indonesia without PPRA at the same time. This study is a cross sectional study with retrospective data collection from the patient's medical record. The analysis was carried out descriptively and analytically with the Chi-square method to see the relationship between rational use of antibiotics and therapeutic outcomes. A single antibiotic which is generally used in one of the hospitals and private hospitals in Indonesia is Ampicillin. In addition, antibiotics that are often prescribed are Ceftriaxone and Cefotaxim). The use of antibiotics in Public Hospitals found 83 irrational use of antibiotics (81,4%) and 75 total uses of antibiotics (86,2%) in Private Hospitals. Irrational category III A (long duration) mostly occurs in two hospitals. The results of the research on the relationship between rationality and therapeutic outcome were analyzed by Chi-square. The results showed that the rationality of empirical antibiotic therapy significantly improved therapeutic outcomes (p=0.008) in one of the hospitals in Indonesia. The results of research conducted in one of the Indonesian private hospitals obtained p value = 0,153.